Be a Mom: Patterns of Program Usage and Acceptability Among Women With Low-Risk and High-Risk for Postpartum Depression - Xavier, Sandra; Monteiro, Fabiana; Canavarro, Maria Cristina; Fonseca, Ana (Frontiers in Global Women's Health, 2022)
Background Be a Mom is a self-guided web-based intervention developed to prevent postpartum depression (PPD) symptoms and to promote maternal wellbeing, respectively among high and low-risk new mothers. This study aims to examine and compare (1) Be a Mom's patterns of usage and (2) Be a Mom's acceptability among women presenting high and low risk for PPD. Methods The sample was composed by 800 women who were randomized to Be a Mom [542 presenting high-risk (Postpartum Depression Predictors Inventory-Revised ≥ 5.5) and 258 presenting low-risk for PPD]. Data regarding patterns of usage were collected through the Be a Mom website. Acceptability data were collected through a brief questionnaire. Results 27.9% of high-risk and 36.3% of low-risk women completed the program. A higher proportion of participants in the low-risk group completed Be a Mom [X(1)2 = 5.29, p = 0.021] and completed more modules [t(723) = −3.01, p = 0.003]. No significant differences were found between the groups in number of logins, minutes spent on the program, exercises completed and number of times audios were played. a higher proportion of women in the high-risk group considered that participating in Be a Mom was too demanding [X(1)2 = 8.21, p = 0.004]. Conclusions Despite the low rates of completion, Be a Mom appears to be an acceptable option for both women with high-risk and low-risk for PPD. Lack of time seems to be the main reason for non-completion, so it is important to develop briefer versions of the program and introduce engagement strategies that may increase completion rate.